A piezoresistive conductive silicone gel with a multi-stage microporous structure and a preparation method thereof
Patent Information
- Application Number
- CN202611414233.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-30
Smart Images

Figure CN123004145A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of conductive silicone sensing materials, specifically to a piezoresistive conductive silicone with a multi-level microporous structure and its preparation method. Background Technology
[0002] Flexible pressure sensing, wearable monitoring, robotic haptics, cushioning pads, and human-machine interface devices all demand elastic conductive materials that combine flexibility, compressibility, stable conductive pathways, and cyclic reliability. Silicone materials possess excellent elastic recovery, strong environmental adaptability, and ease of molding, making them suitable for constructing pressure sensing elements that conform to complex curved surfaces. Conductive carbon black, as a conductive filler, offers advantages such as low cost, wide availability, and good processing adaptability, enabling the formation of a pressure-responsive conductive network within an elastic silicone matrix. However, for piezoresistive responses in the low-to-medium pressure range, the material requires sufficient pore structure to amplify compressive deformation, a complete pore wall framework to maintain resilience and lifespan, and continuous conductive phase in the pore wall region without excessive agglomeration. Therefore, simultaneously controlling the microporous structure, conductive phase dispersion, and curing process within the same silicone system is crucial for improving the application stability and batch consistency of flexible piezoresistive materials.
[0003] Existing conductive silicone rubbers typically achieve piezoresistive response by directly incorporating conductive carbon black into a silicone matrix. However, carbon black has a high surface energy, making it prone to agglomeration during mixing. While agglomerates can locally reduce resistance, they also lead to uneven distribution of the conductive network, dispersion of in-plane resistance, and increased drift after compression cycling. On the other hand, using porous or foamed structures can increase the compressive deformation amplitude, but increased porosity reduces the pore wall bearing area, easily resulting in a loose structure, increased permanent compression deformation, and irreversible rearrangement of conductive pathways. For example, Chinese patent CN105001641A discloses a carbon black-filled piezoresistive conductive silicone rubber composite material and its preparation method. It focuses on carbon black dispersion and piezoresistive conductivity, but still mainly uses a carbon black-filled silicone rubber composite system, failing to fully address the synergistic control issues between hierarchical porous structure, pore wall conductive phase enrichment, and foaming curing window. Related studies also show that carbon black content significantly affects the piezoresistive behavior of silicone rubber composite materials, indicating a sensitive coupling relationship between conductive filler distribution and pressure response. Summary of the Invention
[0004] The purpose of this invention is to provide a piezoresistive conductive silicone with a multi-level microporous structure and its preparation method, thereby solving the problem that it is difficult to simultaneously achieve structural integrity, piezoresistive sensitivity, conductive carbon black dispersion stability and effective conductive contact in current porous conductive silicone.
[0005] This invention achieves a balance between structural integrity and piezoresistive response stability by matching the proportions of conductive carbon black pre-dispersion, silica gel matrix curing, hydroxyl component and deionized water-induced pore formation, and staged foaming and curing. This results in mutual correction between the strength of the pore wall skeleton and its compressive deformation capacity, and allows the conductive phase to form a relatively continuous distribution in the pore wall region without excessive agglomeration.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A piezoresistive conductive silicone with a multi-level microporous structure, using 100 parts by weight of high-viscosity vinyl-terminated dimethyl polysiloxane as the silicone matrix, wherein the piezoresistive conductive silicone is formed by curing and pore formation of a curable mixture comprising the high-viscosity vinyl-terminated dimethyl polysiloxane and the following components: Conductive carbon black-low viscosity vinyl-terminated dimethyl polysiloxane predispersant, wherein the predispersant contains, on average, 12–28 parts by weight of conductive carbon black and 3–10 parts by weight of low viscosity vinyl-terminated dimethyl polysiloxane. 1.0–5.0 parts by weight of polymethylhydrosiloxane; Hydroxyl-terminated polydimethylsiloxane 0.20–3.00 parts by weight; 1,3-Divinyl-1,1,3,3-Tetramethyldisiloxane platinum (0), in platinum amounts to 5–50 ppm of the total mass of the curable mixture; 0.01–0.20 parts by weight of 1-ethynyl-1-cyclohexanol; 0.10–1.20 parts by weight of deionized water; In the pre-dispersion, the mass ratio of low-viscosity vinyl-terminated dimethyl polysiloxane to conductive carbon black is 15:100 to 60:100; The piezoresistive conductive silicone has a multi-level microporous structure consisting of primary micropores and secondary pore windows.
[0007] Furthermore, the D50 of the primary micropores is 80–350 μm, the D50 of the secondary pore windows is 5–40 μm, the porosity is 35–65 vol%, and the volume resistivity is 10 Ω·cm. 2 -10 5 Ω·cm.
[0008] Furthermore, the pre-dispersion is prepared through the following steps: A1. Dry 100 parts by weight of conductive carbon black at 100–120℃ for 1–3 hours; A2. The conductive carbon black obtained in step A1 is mixed with 15–60 parts by weight of low viscosity vinyl-terminated dimethyl polysiloxane and sheared and wetted at 25–60°C for 0.5–3.0 h to form a carbon black wetted product. A3. The carbon black wetted material is dispersed through a three-roller system 2–5 times, with a roller gap of 20–80 μm; A4. Vacuum degassing for 10–30 min under conditions of -0.09 to -0.06 MPa; A5. Vacuum dry at 40–80℃ for 2–8 h to obtain the pre-dispersion.
[0009] Furthermore, steps A2 to A5 are non-aqueous phase treatment steps; the D90 of the carbon black agglomerates in the pre-dispersion is 2–25 μm.
[0010] Furthermore, the piezoresistive conductive silicone has a pore structure in which adjacent primary micropores are connected through the secondary pore windows.
[0011] Furthermore, the molar ratio of the Si-H groups in the polymethylhydrosiloxane to the total amount of vinyl groups in the high-viscosity vinyl-terminated dimethyl polysiloxane and the low-viscosity vinyl-terminated dimethyl polysiloxane is 0.80–1.80, and the mass ratio of the hydroxyl-terminated polydimethyl siloxane to the polymethylhydrosiloxane is 0.05–0.80; the molar ratio is calculated based on the molar amount of Si-H groups in the polymethylhydrosiloxane used to the total molar amount of vinyl groups in the high-viscosity vinyl-terminated dimethyl polysiloxane and the low-viscosity vinyl-terminated dimethyl polysiloxane used.
[0012] Furthermore, the piezoresistive conductive silicone has at least one of the following product forms or performance characteristics: a. The piezoresistive conductive silicone is a sheet or pad material with a thickness of 0.50–6.00 mm; b. The piezoresistive conductive silicone rubber exhibits a piezoresistive sensitivity of 0.005–0.080 kPa within a pressure range of 10–100 kPa. -1 The coefficient of variation of in-plane resistivity is 5–25%, and the initial resistivity drift rate after 10,000–100,000 compression cycles is 5–30%. c. The piezoresistive conductive silicone has a compression modulus of 20–300 kPa and a compression set of 5–30% in the pressure range of 10–100 kPa.
[0013] This invention employs a design of a pore-forming system using conductive carbon black-low viscosity vinyl-terminated dimethyl polysiloxane pre-dispersion and high viscosity vinyl-terminated dimethyl polysiloxane curing. This system primarily aims to achieve a synergistic balance between pore wall structural integrity and piezoresistive sensitivity. In existing technologies, increasing the degree of crosslinking or reducing the degree of porosity is typically used to improve the strength of the pore wall framework, but this limits compressive deformation and weakens the resistive response. Conversely, increasing the degree of porosity or reducing the pore wall deformation resistance is often used to improve piezoresistive sensitivity, but this can easily lead to a loose structure and irreversible rearrangement of conductive pathways. This invention, through conductive carbon black pre-dispersion, hydroxyl-terminated polydimethylsiloxane and deionized water-induced pore formation, polymethylhydrosiloxane curing, and platinum catalytic window regulation, achieves mutual correction between conductive phase distribution, pore window connectivity, and pore wall load-bearing capacity, thereby balancing structural integrity, conductive uniformity, and pressure response stability.
[0014] This invention also discloses a method for preparing piezoresistive conductive silicone with a multi-level microporous structure, comprising the following steps: S1. Provides a conductive carbon black-low viscosity vinyl-terminated dimethyl polysiloxane predispersant obtained through non-aqueous phase treatment; S2. Mix 100 parts by weight of high viscosity vinyl-terminated dimethyl polysiloxane with the pre-dispersion and stir at 20–50°C for 10–60 min to obtain a conductive silicone premix. S3. Polymethylhydrosiloxane, hydroxyl-terminated polydimethylsiloxane and deionized water are added sequentially to the conductive silicone premix, followed by the addition of 1-ethynyl-1-cyclohexanol and 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0), and the mixture is mixed at 20–40°C for 5–30 min to obtain a curable mixture; S4. The curable mixture is introduced into a molding device and foamed and cured in stages at 70–130°C for 8–40 min to obtain pre-cured multi-level microporous conductive silicone. S5. The pre-cured multi-level microporous conductive silicone is post-cured at 120–170℃ for 0.5–4.0h, and then placed at 60–100℃ for ventilation treatment for 1–8h to obtain a piezoresistive conductive silicone with a multi-level microporous structure.
[0015] Furthermore, it possesses at least one of the following process characteristics: a. The stirring in step S2 is planetary stirring, kneading stirring or double planetary vacuum stirring. After stirring, degassing is carried out under conditions of -0.09 to -0.06 MPa for 5–30 min. b. In step S3, the order of adding the polymethylhydrosiloxane, the hydroxyl-terminated polydimethylsiloxane, and the deionized water is as follows: first add the polymethylhydrosiloxane, then add the hydroxyl-terminated polydimethylsiloxane, and finally add the deionized water. The total addition time for the three is 3–20 min.
[0016] Furthermore, step S4 includes a first stage and a second stage, wherein the first stage is maintained at 70–95°C for 3–15 min and the second stage is maintained at 95–130°C for 5–25 min.
[0017] Furthermore, when the molding device used in step S4 is a mold, the closing pressure of the mold is 0.05–1.00 MPa, and the thickness of the mold cavity is 0.50–6.00 mm.
[0018] Furthermore, step S4 employs continuous calendering, molding, or injection molding, and the time from the completion of step S3 to entering step S4 for the curable mixture is 1–30 min.
[0019] This invention employs a pre-dispersion preparation process, conductive silicone premixing, sequential feeding, staged foaming and curing, post-curing, and ventilation treatment. It is primarily used to achieve, fix, or amplify the aforementioned synergistic effects. Existing processes, if only enhanced mixing and dispersion, easily weaken the effective contact between carbon black particles; if only the degree of foaming is increased, it can lead to insufficient pore wall bearing capacity and resistance drift. This invention controls the wetting and agglomeration scale of conductive carbon black through A1 to A5 non-aqueous phase pretreatment. Then, through S2 premixing, S3 sequential addition of polymethylhydrosiloxane, hydroxyl-terminated polydimethylsiloxane, and deionized water, and the staged foaming and curing process in S4 gradually fixes the multi-level microporous structure, matching the pore-forming process, cross-linking process, and conductive phase migration process. This ensures that the piezoresistive conductive silicone maintains coordination between the processing window, pore structure stability, and pressure response.
[0020] The conductive carbon black-low viscosity vinyl-terminated dimethyl polysiloxane predispersant primarily addresses the issues of conductive carbon black wetting and dispersion, as well as the continuity of conductive pathways on the pore walls. The curing and pore-forming process using hydroxyl-terminated polydimethylsiloxane, polymethylhydrosiloxane, and deionized water mainly addresses the issues of multi-level microporous structures and amplified compressive deformation. Simply increasing the conductive carbon black content in the predispersant, while enhancing conductive contact, may impair pore structure uniformity due to agglomeration and increased rheology. Conversely, simply increasing the degree of pore formation, while enhancing piezoresistive response, may lead to insufficient pore wall load-bearing capacity and resistance drift. This invention, through predisposition wetting, non-aqueous phase treatment, sequential feeding, and staged curing, achieves a controlled distribution of the conductive phase towards the pore wall region, and enables primary micropores and secondary pore windows to collaboratively bear deformation transmission, ultimately balancing structural integrity and piezoresistive response stability.
[0021] Beneficial technical effects 1. By first forming a pre-dispersion with low-viscosity vinyl-terminated dimethyl polysiloxane and then introducing a high-viscosity vinyl-terminated dimethyl polysiloxane matrix, the local agglomeration tendency when carbon black is directly added can be reduced, making it easier for the conductive phase to be distributed in the pore wall region, thereby improving the uniformity of in-plane resistivity and the repeatability of piezoresistive response.
[0022] 2. By combining polymethylhydrosiloxane, hydroxyl-terminated polydimethylsiloxane, deionized water, platinum catalyst and 1-ethynyl-1-cyclohexanol, the pore-forming rate and cross-linking rate can be coordinated during the curing process, reducing the instability caused by excessive collapse or over-connection of the pore structure, and enabling the material to take into account both compression rebound and compressive resistance changes.
[0023] 3. The multi-level microporous structure composed of primary micropores and secondary pore windows enables a more continuous response process for pore wall deformation, pore window connectivity, and conductive path rearrangement under pressure. This avoids local collapse caused by a single large pore structure and also avoids insufficient deformation of dense conductive silicone, thereby improving the application adaptability in the medium and low pressure range.
[0024] 4. By using A1 to A5 non-aqueous phase pretreatment, three-roll dispersion, vacuum degassing and vacuum drying, the size of conductive carbon black agglomerates can be controlled before adding the foaming and curing system, providing a process basis for the subsequent distribution of conductive phase on the pore walls and batch-to-batch consistency.
[0025] 5. Through staged foaming and curing, post-curing and further ventilation treatment, sheet or pad-shaped piezoresistive conductive silicone can maintain a relatively stable pore structure and resistance distribution in the thickness direction and in-plane direction, reducing the risk of initial resistance drift after long-term compression cycles, making it suitable for flexible pressure sensing and buffer contact scenarios. Attached Figure Description
[0026] Figure 1 The particle size distribution diagrams are shown for the conductive carbon black agglomerates in the pre-dispersions of Example 1 and Comparative Example 6, and the conductive silicone premix obtained after mixing in step S2 of Comparative Example 9.
[0027] Figure 2 The graph shows the change in initial resistance drift rate after compression cycling for Examples 1, 8, and 10.
[0028] Figure 3 The graph shows the change in D50 of the primary micropores after compression cycles in Examples 1, 8, and 10.
[0029] Figure 4 The diagram shows the changes in the secondary aperture D50 after compression cycles in Examples 1, 8, and 10.
[0030] Figure 5 The graph shows the coefficient of variation of in-plane resistance for Examples 1, 8, and 9.
[0031] Figure 6 The pressure-relative resistance change response curves are for Examples 1 to 4.
[0032] Figure 7The diagram shows the influence of different conductive carbon black equivalent amounts on the piezoresistive sensitivity and initial resistance drift rate of samples prepared using the basic formulation and process of Example 1.
[0033] Figure 8 This is a comparison of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 9; wherein, Figure 8 Figure a in the figure is a macroscopic optical photograph of the final product of Example 1, which is a black sheet-like piezoresistive conductive silicone with a nominal thickness of 0.50 mm. Figure 8 Figure b in the figure is a macroscopic optical photograph of the final product of Comparative Example 9. The final product is a sheet-like piezoresistive conductive silicone obtained without undergoing the preparation process of conductive carbon black-low viscosity vinyl-terminated dimethyl polysiloxane predispersant.
[0034] Figure 9 The images show a comparison of the scanning electron microscope morphology of the final product of Example 1 and the final product of Comparative Example 9; wherein, Figure 9 Figure a in the image is a low-magnification scanning electron microscope image of the final product of Example 1; Figure 9 Figure b in the figure is a low-magnification scanning electron microscope image of the final product of Comparative Example 9; Figure 9 Figure c in the image is a medium-magnification scanning electron microscope image of the final product of Example 1; Figure 9 Figure d in the image is a medium-magnification scanning electron microscope image of the final product of Comparative Example 9. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0036] Example 1 In terms of overall preparation scale and product form, this embodiment uses 100.00g of high-viscosity vinyl-terminated dimethyl polysiloxane as the main matrix to prepare sheet-like piezoresistive conductive silicone. The high-viscosity vinyl-terminated dimethyl polysiloxane is a commercially available silicone base polymer with volatile matter ≤1.0% and moisture ≤0.05%. The conductive carbon black is a commercially available conductive grade carbon black with ash content ≤0.5%, and the initial agglomerates are dried before use. The low-viscosity vinyl-terminated dimethyl polysiloxane is a commercially available fluid-type siloxane with moisture ≤0.05%. Polymethylhydrosiloxane, hydroxyl-terminated polydimethylsiloxane, 1-ethynyl-1-cyclohexanol, and deionized water are all commercially available raw materials. 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0) is added in the form of a platinum-containing mother liquor, making the platinum content 5 ppm based on the total mass of the curable mixture.
[0037] Raw material, component, or material specifications: Conductive carbon black (calculated usage): 12.00 g; Low-viscosity vinyl-terminated dimethyl polysiloxane (calculated usage): 3.00 g; Polymethylhydrosiloxane (calculated usage): 4.00 g; Hydroxyl-terminated polydimethylsiloxane (calculated usage): 0.20 g; 1-ethynyl-1-cyclohexanol (calculated usage): 0.01 g; Deionized water (calculated usage): 0.10 g. The mass ratio of hydroxyl-terminated polydimethylsiloxane to polymethylhydrosiloxane is 0.05. The molar ratio of Si-H groups in polymethylhydrosiloxane to the total vinyl groups in both high-viscosity and low-viscosity vinyl-terminated dimethyl polysiloxane is controlled at 0.80.
[0038] Step 1: Conductive carbon black pretreatment. Weigh 100.00 g of conductive carbon black and dry it in a 100℃ forced-air drying oven for 1 hour. After removal, place it in a desiccator and cool it to 25℃. Add the dried conductive carbon black and 25.00 g of low-viscosity vinyl-terminated dimethyl polysiloxane to a jacketed mixing container and shear and wet it at 1200 rpm for 0.5 hours at 25℃ to obtain a carbon black wetted material. Disperse the carbon black wetted material twice using a three-roller mixer with a roller gap of 80 μm. Then, degas it under vacuum at -0.06 MPa for 10 minutes and vacuum dry it at 40℃ for 2 hours to obtain a conductive carbon black-low-viscosity vinyl-terminated dimethyl polysiloxane predispersant. The carbon black agglomerate D90 in the predispersant is 25 μm.
[0039] Step 2: Preparation of conductive silicone premix. Add 100.00g of high-viscosity vinyl-terminated dimethyl polysiloxane to a planetary stirring vessel. Add a pre-dispersion containing 12.00g of conductive carbon black and 3.00g of low-viscosity vinyl-terminated dimethyl polysiloxane at 20°C. Stir at 35rpm revolution and 800rpm dispersion speed for 10min. After stirring, degas at -0.06MPa for 5min. The degassing endpoint is when no continuous large bubbles escape from the material surface, yielding the conductive silicone premix.
[0040] Step 3: Preparation of the curable mixture. At 20°C, first add 4.00 g of polymethylhydrosiloxane to the conductive silicone premix and stir for 1 min; then add 0.20 g of hydroxyl-terminated polydimethylsiloxane and stir for 1 min; finally add 0.10 g of deionized water, with a total addition time of 3 min. Next, add 0.01 g of 1-ethynyl-1-cyclohexanol and 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0) mother liquor to achieve a platinum content of 5 ppm, and continue mixing for 5 min. The mixing endpoint is a slurry with uniform color, no visible carbon black particles or clumps, and no obvious streaks after being spread by a scraper.
[0041] Step 4: Molding, foaming, curing, and post-treatment. The curable mixture is poured into the mold within 1 minute of completing Step 3. The mold cavity thickness is 0.50 mm, and the mold closing pressure is 0.05 MPa. Foaming and curing employ a two-stage process: the first stage is held at 70℃ for 3 minutes, and the second stage is held at 95℃ for 5 minutes, yielding pre-cured multi-level microporous conductive silicone. The pre-cured multi-level microporous conductive silicone is then post-cured at 120℃ for 0.5 hours, followed by ventilation treatment at 60℃ for 1 hour to obtain sheet-like piezoresistive conductive silicone.
[0042] Quality testing methods and results: After equilibration at 25℃ and 50% relative humidity for 24 hours, the sheet material of this embodiment was tested. Optical microscopic images showed at least 300 pore structure units, with a primary micropore D50 of 80±6μm, a secondary pore window D50 of 5.0±0.6μm, and a porosity of 35.0±1.2 vol%. The volume resistivity, measured using the clamped electrode method, was 1.0×10⁻⁶. 5 ±0.08×10 5 Ω·cm. Ten measuring points are arranged in the in-plane direction, and the coefficient of variation of in-plane resistance is 25.0±1.4%. The piezoresistive sensitivity is 0.005±0.001kPa within the pressure range of 10–100kPa. -1 After 10,000 compression cycles, the initial resistivity drift rate is 30.0±1.8%, the compression modulus is 300±12 kPa, and the compression permanent deformation rate is 5.0±0.6%.
[0043] Features and application scenarios of this embodiment: This embodiment adopts a lower amount of conductive carbon black, a lower amount of deionized water, and a thinner sheet design. The pore structure is more compact and the compression modulus is higher, making it suitable for flexible pressure sensing sheets with high requirements for support, thin fit, and low deformation buffer contact.
[0044] Example 2 Raw materials and proportions: A pad-shaped piezoresistive conductive silicone was prepared based on 100.00g of high-viscosity vinyl-terminated dimethyl polysiloxane as the main matrix. The equivalent amount of conductive carbon black was 28.00g, the equivalent amount of low-viscosity vinyl-terminated dimethyl polysiloxane was 10.00g, the amount of polymethylhydrosiloxane was 5.00g, the amount of hydroxyl-terminated polydimethylsiloxane was 3.00g, the amount of 1-ethynyl-1-cyclohexanol was 0.20g, the amount of deionized water was 1.20g, and 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0) was added to 50ppm of the total mass of the curable mixture based on platinum. The mass ratio of hydroxyl-terminated polydimethylsiloxane to polymethylhydrosiloxane was 0.60. The molar ratio of the Si-H groups in polymethylhydrosiloxane to the total amount of vinyl groups in high-viscosity vinyl-terminated dimethyl polysiloxane and low-viscosity vinyl-terminated dimethyl polysiloxane is 1.80.
[0045] The pre-dispersion preparation process involved drying 100.00 g of conductive carbon black at 120 °C for 3 h, cooling it to 25 °C, and then mixing it with 35.70 g of low-viscosity vinyl-terminated dimethyl polysiloxane. The mixture was then sheared and wetted at 1500 rpm for 3.0 h at 60 °C to form a carbon black wetted material. This material was dispersed five times using a three-roll mill with a roller gap of 20 μm. After dispersion, the material was degassed under vacuum at -0.09 MPa for 30 min and then vacuum dried at 80 °C for 8 h to obtain the pre-dispersion. The carbon black agglomerates in the pre-dispersion had a D90 of 2 μm.
[0046] In the main mixing process, 100.00 g of high-viscosity vinyl-terminated dimethyl polysiloxane and a pre-dispersion containing 28.00 g of conductive carbon black and 10.00 g of low-viscosity vinyl-terminated dimethyl polysiloxane were added to a dual planetary vacuum mixer and stirred at 50 °C for 60 min at a revolution speed of 45 rpm and a dispersion speed of 1000 rpm. After stirring, the mixture was degassed at -0.09 MPa for 30 min to obtain a conductive silicone premix.
[0047] In the post-processing, 5.00 g of polymethylhydrosiloxane, 3.00 g of hydroxyl-terminated polydimethylsiloxane, and 1.20 g of deionized water were added to the conductive silicone premix at 40°C, with a total addition time of 20 min. Then, 0.20 g of 1-ethynyl-1-cyclohexanol and 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0) mother liquor were added, and mixing continued for 30 min to obtain a curable mixture. The curable mixture was poured into a mold within 30 min after mixing, with a mold cavity thickness of 6.00 mm and a closing pressure of 1.00 MPa. The first stage was maintained at 95°C for 15 min, and the second stage at 130°C for 25 min, yielding a pre-cured multi-level microporous conductive silicone. This was then post-cured at 170°C for 4.0 h and ventilated at 100°C for 8 h to obtain a pad-shaped piezoresistive conductive silicone.
[0048] For quality inspection or performance testing, the sample was cut into 30mm × 30mm gaskets and equilibrated for 24 hours at 25℃ and 50% relative humidity. Statistical results from microscopic images showed that the primary micropore D50 was 350±18μm, the secondary pore window D50 was 40±3μm, and the porosity was 65.0±1.8 vol%. The volume resistivity was 1.0×10⁻⁶. 2 ±0.1×10 2 Ω·cm. With 100 measuring points arranged in the in-plane direction, the in-plane resistance variation coefficient is 18.0±1.1%. The piezoresistive sensitivity is 0.080±0.004kPa within the pressure range of 10–100kPa. -1After 100,000 compression cycles, the initial resistivity drift rate is 5.0±0.5%, the compression modulus is 20±3 kPa, and the compression set is 30.0±1.6%.
[0049] The features of this embodiment are that it uses a higher amount of conductive carbon black and a higher amount of pore-forming components, resulting in a thicker sheet and a more open pore structure. This makes it suitable for flexible pad-shaped sensing scenarios that require a higher pressure response amplitude, a thicker buffer contact layer, and a lower modulus.
[0050] Example 3 In this embodiment, a medium-thickness sheet-like piezoresistive conductive silicone was prepared using 100.00g of high-viscosity vinyl-terminated dimethyl polysiloxane as the main matrix. The key proportions were: 20.00g conductive carbon black, 3.00g low-viscosity vinyl-terminated dimethyl polysiloxane, 1.00g polymethylhydrosiloxane, 0.80g hydroxyl-terminated polymethyl polysiloxane, 0.60g deionized water, 0.08g 1-ethynyl-1-cyclohexanol, and a platinum content of 20ppm based on the total mass of the curable mixture. The mass ratio of hydroxyl-terminated polymethyl polysiloxane to polymethylhydrosiloxane was 0.80. The molar ratio of the Si-H groups in polymethylhydrosiloxane to the total vinyl groups in both the high-viscosity and low-viscosity vinyl-terminated dimethyl polysiloxane was 1.10.
[0051] S1. Preparation of the pre-dispersion: 100.00 g of conductive carbon black was dried at 110 °C for 2 h, and mixed with 15.00 g of low-viscosity vinyl-terminated dimethyl polysiloxane. The mixture was sheared and wetted at 40 °C for 1.5 h to form a carbon black wetted material. The carbon black wetted material was dispersed three times using a three-roller with a roller gap of 50 μm. Subsequently, it was degassed under vacuum at -0.08 MPa for 20 min and then vacuum dried at 60 °C for 4 h to obtain the pre-dispersion. The carbon black agglomerates in the pre-dispersion had a D90 of 10 μm.
[0052] S2. Premixing and Degassing: 100.00g of high-viscosity vinyl-terminated dimethyl polysiloxane and a pre-dispersion containing 20.00g of conductive carbon black and 3.00g of low-viscosity vinyl-terminated dimethyl polysiloxane were added to a kneading mixer and stirred at 35°C for 30 minutes at a kneading paddle speed of 60 rpm. After stirring, degassing was performed at -0.08MPa for 15 minutes to obtain a conductive silicone premix.
[0053] S3. Formation of the curable mixture: At 30°C, 1.00 g of polymethylhydrosiloxane, 0.80 g of hydroxyl-terminated polydimethylsiloxane, and 0.60 g of deionized water were added to the conductive silicone premix. The total addition time was 10 min. Then, 0.08 g of 1-ethynyl-1-cyclohexanol and a 20 ppm platinum content 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0) mother liquor were added and mixed for 15 min to obtain the curable mixture. The mixing endpoint was a uniform film thickness with no visible dry powder lumps.
[0054] S4. Curing and molding: Within 10 minutes after completing step S3, the curable mixture is introduced into a molding die. The die cavity thickness is 2.50 mm, and the closing pressure is 0.40 MPa. Foaming and curing are divided into two stages: the first stage is maintained at 80°C for 8 minutes, and the second stage is maintained at 115°C for 12 minutes, resulting in pre-cured multi-level microporous conductive silicone.
[0055] S5. Heat Treatment and Quality Control: The initially cured multi-level microporous conductive silicone was post-cured at 150℃ for 2 hours, followed by ventilation treatment at 80℃ for 4 hours. Samples were then placed at 25℃ and 50% relative humidity for 24 hours before testing. The first-level micropore D50 was 180±10μm, the second-level pore window D50 was 18±2μm, the porosity was 50.0±1.5 vol%, and the volume resistivity was 8.0×10⁻⁶. 3 ±0.5×10 3 Ω·cm. Fifty measuring points are arranged in the in-plane direction, and the coefficient of variation of in-plane resistance is 10.0±0.8%. The piezoresistive sensitivity is 0.040±0.003kPa within the pressure range of 10–100kPa. -1 After 50,000 compression cycles, the initial resistivity drift rate is 15.0±1.2%, the compression modulus is 120±8 kPa, and the compression set is 15.0±1.0%.
[0056] The applicable scenario of this embodiment is that it uses a medium amount of conductive carbon black and a relatively high ratio of hydroxyl-terminated polydimethylsiloxane, and the process conditions are biased towards the medium and mild range, which is suitable for flexible pressure sensing pads that require uniform conductivity, resilience and processing stability.
[0057] Example 4 I. Preparation Object and Variable Configuration: A sheet-like piezoresistive conductive silicone with a thickness of 4.00 mm was prepared using 100.00 g of high-viscosity vinyl-terminated dimethyl polysiloxane as the main matrix. The equivalent amount of conductive carbon black was 16.00 g, the equivalent amount of low-viscosity vinyl-terminated dimethyl polysiloxane was 9.60 g, the amount of polymethylhydrosiloxane was 2.50 g, the amount of hydroxyl-terminated polymethyl polysiloxane was 2.00 g, the amount of deionized water was 0.90 g, the amount of 1-ethynyl-1-cyclohexanol was 0.12 g, and the platinum content was 35 ppm based on the total mass of the curable mixture. The mass ratio of hydroxyl-terminated polymethyl polysiloxane to polymethylhydrosiloxane was 0.80. The molar ratio of the Si-H groups in polymethylhydrosiloxane to the total vinyl groups in both the high-viscosity and low-viscosity vinyl-terminated dimethyl polysiloxane was 1.40.
[0058] II. Obtaining the Predispersion: 100.00 g of conductive carbon black was dried at 115 °C for 2.5 h. After cooling, it was mixed with 60.00 g of low-viscosity vinyl-terminated dimethyl polysiloxane and sheared and wetted at 55 °C for 2.5 h to form a carbon black wetted material. The carbon black wetted material was dispersed four times using a three-roller with a roller gap of 30 μm. Then, it was degassed under vacuum at -0.07 MPa for 25 min and vacuum dried at 70 °C for 6 h to obtain the predispersion. The carbon black agglomerates in the predispersion had a D90 of 6 μm.
[0059] III. Mixing and Reaction Window Control: 100.00g of high-viscosity vinyl-terminated dimethyl polysiloxane and a pre-dispersion containing 16.00g of conductive carbon black and 9.60g of low-viscosity vinyl-terminated dimethyl polysiloxane were added to a dual planetary vacuum mixer and stirred at 45℃ for 45min at a revolution speed of 40rpm and a dispersion speed of 900rpm. Then, the mixture was degassed at -0.07MPa for 20min. 2.50g of polymethylhydrosiloxane, followed by 2.00g of hydroxyl-terminated polydimethylsiloxane, and finally 0.90g of deionized water were added to the obtained conductive silicone premix. The total addition time was 15min. Then, 0.12g of 1-ethynyl-1-cyclohexanol and 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0) mother liquor were added and mixed at 35℃ for 20min to obtain a curable mixture.
[0060] IV. Molding and Heat Treatment: The curable mixture is continuously calendered within 20 minutes after mixing and then introduced into the molding zone. The mold cavity thickness is 4.00 mm, and the closing pressure is 0.70 MPa. Foaming and curing follow a procedure of holding the first stage at 90°C for 10 minutes and the second stage at 125°C for 20 minutes. After demolding, the pre-cured multi-level microporous conductive silicone is post-cured at 160°C for 3 hours and then ventilated at 90°C for 6 hours.
[0061] V. Test Results and Application Directions: The sample was equilibrated at 25℃ and 50% relative humidity for 24 hours. Statistical analysis of the images showed that the primary micropore D50 was 260±14μm, the secondary pore window D50 was 30±2μm, the porosity was 58.0±1.6 vol%, and the volume resistivity was 5.0×10⁻⁶. 2 ±0.4×10 2 Ω·cm. Eighty measuring points are arranged in the in-plane direction, and the coefficient of variation of in-plane resistance is 5.0 ± 0.4%. The piezoresistive sensitivity is 0.060 ± 0.004 kPa within the pressure range of 10–100 kPa. -1 After 80,000 compression cycles, the initial resistance drift rate is 8.0±0.7%, the compression modulus is 80±6 kPa, and the compression set is 12.0±0.8%. This embodiment is suitable for wearable piezoresistive components that require high resistance consistency, long cycle life, and moderately soft touch.
[0062] Comparative Example 1: Basically the same as Example 1, except that the amount of conductive carbon black was adjusted to 8.00 parts by weight, and other conditions were kept the same: 100.00 parts by weight of high-viscosity vinyl-terminated dimethyl polysiloxane, 3.00 parts by weight of low-viscosity vinyl-terminated dimethyl polysiloxane, 4.00 parts by weight of polymethylhydrosiloxane, 0.20 parts by weight of hydroxyl-terminated polydimethylsiloxane, 0.01 parts by weight of 1-ethynyl-1-cyclohexanol, 0.10 parts by weight of deionized water, 5 ppm platinum content, A2 shear wetting at 25°C for 0.5 h, A3 three-roll dispersion twice with an 80 μm roller gap, S2 stirring at 20°C for 10 min, S3 mixing at 20°C for 5 min, S4 first stage at 70°C for 3 min, S4 second stage at 95°C for 5 min, S5 post-curing at 120°C for 0.5 h, and 1 h of ventilation treatment at 60°C.
[0063] Comparative Example 2: Basically the same as Example 1, except that the equivalent amount of conductive carbon black was adjusted to 34.00 parts by weight, and other conditions were kept the same: 100.00 parts by weight of high-viscosity vinyl-terminated dimethyl polysiloxane, 3.00 parts by weight of low-viscosity vinyl-terminated dimethyl polysiloxane, 4.00 parts by weight of polymethylhydrosiloxane, 0.20 parts by weight of hydroxyl-terminated polydimethylsiloxane, 0.01 parts by weight of 1-ethynyl-1-cyclohexanol, 0.10 parts by weight of deionized water, 5 ppm platinum content, A2 shear wetting at 25°C for 0.5 h, A3 three-roll dispersion twice with an 80 μm roller gap, S2 stirring at 20°C for 10 min, S3 mixing at 20°C for 5 min, S4 first stage at 70°C for 3 min, S4 second stage at 95°C for 5 min, S5 post-curing at 120°C for 0.5 h, and 1 h of ventilation treatment at 60°C.
[0064] Comparative Example 3: Basically the same as Example 1, except that the amount of polymethylhydrosiloxane was adjusted to 0.50 parts by weight, and other conditions were kept the same: 100.00 parts by weight of high-viscosity vinyl-terminated dimethyl polysiloxane, 12.00 parts by weight of conductive carbon black, 3.00 parts by weight of low-viscosity vinyl-terminated dimethyl polysiloxane, 0.20 parts by weight of hydroxyl-terminated polydimethyl siloxane, 0.01 parts by weight of 1-ethynyl-1-cyclohexanol, 0.10 parts by weight of deionized water, 5 ppm platinum content, A2 shear wetting at 25°C for 0.5 h, A3 three-roll dispersion twice with an 80 μm roller gap, S2 stirring at 20°C for 10 min, S3 mixing at 20°C for 5 min, S4 first stage at 70°C for 3 min, S4 second stage at 95°C for 5 min, S5 post-curing at 120°C for 0.5 h, and 1 h of ventilation treatment at 60°C.
[0065] Comparative Example 4: Basically the same as Example 1, except that the amount of deionized water was adjusted to 1.80 parts by weight, and other conditions were kept the same: 100.00 parts by weight of high-viscosity vinyl-terminated dimethyl polysiloxane, 12.00 parts by weight of conductive carbon black, 3.00 parts by weight of low-viscosity vinyl-terminated dimethyl polysiloxane, 4.00 parts by weight of polymethylhydrosiloxane, 0.20 parts by weight of hydroxyl-terminated polydimethylsiloxane, 0.01 parts by weight of 1-ethynyl-1-cyclohexanol, 5 ppm platinum content, A2 shear wetting at 25°C for 0.5 h, A3 three-roll dispersion twice with an 80 μm roller gap, S2 stirring at 20°C for 10 min, S3 mixing at 20°C for 5 min, S4 first stage at 70°C for 3 min, S4 second stage at 95°C for 5 min, S5 post-curing at 120°C for 0.5 h, and 1 h of ventilation treatment at 60°C.
[0066] Comparative Example 5: Basically the same as Example 1, except that the temperature of the first stage in step S4 is adjusted to 65°C, and other conditions are maintained as follows: 100.00 parts by weight of high viscosity vinyl-terminated dimethyl polysiloxane, 12.00 parts by weight of conductive carbon black, 3.00 parts by weight of low viscosity vinyl-terminated dimethyl polysiloxane, 4.00 parts by weight of polymethylhydrosiloxane, 0.20 parts by weight of hydroxyl-terminated polydimethylsiloxane, 0.01 parts by weight of 1-ethynyl-1-cyclohexanol, 0.10 parts by weight of deionized water, 5 ppm platinum content, A2 shear wetting at 25°C for 0.5 h, A3 three-roller dispersion twice with an 80 μm roller gap, S2 stirring at 20°C for 10 min, S3 mixing at 20°C for 5 min, S4 first stage holding for 3 min, S4 second stage at 95°C for 5 min, S5 post-curing at 120°C for 0.5 h, and 1 h of ventilation treatment at 60°C.
[0067] Comparative Example 6: Basically the same as Example 1, except that the number of three-roller dispersion passes in step A3 was adjusted to 1 pass, while other conditions remained the same: 100.00 parts by weight of high-viscosity vinyl-terminated dimethyl polysiloxane, 12.00 parts by weight of conductive carbon black, 3.00 parts by weight of low-viscosity vinyl-terminated dimethyl polysiloxane, 4.00 parts by weight of polymethylhydrosiloxane, 0.20 parts by weight of hydroxyl-terminated polydimethylsiloxane, 0.01 parts by weight of 1-ethynyl-1-cyclohexanol, 0.10 parts by weight of deionized water, 5 ppm platinum content, A2 shear wetting at 25°C for 0.5 h, A3 roller gap of 80 μm, S2 stirring at 20°C for 10 min, S3 mixing at 20°C for 5 min, S4 first stage at 70°C for 3 min, S4 second stage at 95°C for 5 min, S5 post-curing at 120°C for 0.5 h, and 1 h of ventilation treatment at 60°C.
[0068] Comparative Example 7: Basically the same as Example 1, except that the order of addition in step S3 is adjusted to first add deionized water, then polymethylhydrosiloxane, and finally hydroxyl-terminated polydimethylsiloxane. The total addition time for all three is 3 minutes. Other conditions are maintained as follows: 100.00 parts by weight of high-viscosity vinyl-terminated dimethylpolysiloxane, 12.00 parts by weight of conductive carbon black, 3.00 parts by weight of low-viscosity vinyl-terminated dimethylpolysiloxane, 4.00 parts by weight of polymethylhydrosiloxane, and hydroxyl-terminated... Polydimethylsiloxane 0.20 parts by weight, 1-ethynyl-1-cyclohexanol 0.01 parts by weight, deionized water 0.10 parts by weight, platinum content 5 ppm, A2 shear wetting at 25℃ for 0.5 h, A3 three-roller dispersion twice with an 80 μm roller gap, S2 stirring at 20℃ for 10 min, S3 mixing at 20℃ for 5 min, S4 first stage at 70℃ for 3 min, S4 second stage at 95℃ for 5 min, S5 post-curing at 120℃ for 0.5 h, 60℃ ventilation treatment for 1 h.
[0069] Comparative Example 8: Basically the same as Example 1, except that no ventilation treatment is performed after step S5. Other conditions are maintained as follows: 100.00 parts by weight of high viscosity vinyl-terminated dimethyl polysiloxane, 12.00 parts by weight of conductive carbon black, 3.00 parts by weight of low viscosity vinyl-terminated dimethyl polysiloxane, 4.00 parts by weight of polymethylhydrosiloxane, 0.20 parts by weight of hydroxyl-terminated polydimethylsiloxane, 0.01 parts by weight of 1-ethynyl-1-cyclohexanol, 0.10 parts by weight of deionized water, 5 ppm platinum content, A2 shear wetting at 25°C for 0.5 h, A3 three-roller dispersion twice with an 80 μm roller gap, S2 stirring at 20°C for 10 min, S3 mixing at 20°C for 5 min, S4 first stage at 70°C for 3 min, S4 second stage at 95°C for 5 min, and S5 post-curing at 120°C for 0.5 h.
[0070] Comparative Example 9: Essentially the same as Example 1, except that instead of preparing a conductive carbon black-low viscosity vinyl-terminated dimethyl polysiloxane predispersant, in step S2, 12.00 parts by weight of conductive carbon black dried at 100°C for 1 hour and 3.00 parts by weight of low viscosity vinyl-terminated dimethyl polysiloxane were separately added to high viscosity vinyl-terminated dimethyl polysiloxane and mixed. Other conditions were maintained as follows: 4.00 parts by weight of polymethylhydrosiloxane and hydroxyl-terminated polydimethylsiloxane. The mixture consisted of 0.20 parts by weight of alkylene, 0.01 parts by weight of 1-ethynyl-1-cyclohexanol, 0.10 parts by weight of deionized water, and 5 ppm of platinum. The reaction process was as follows: S2 - stirring at 20°C for 10 min; S3 - adding polymethylhydrosiloxane, hydroxyl-terminated polydimethylsiloxane, and deionized water in that order for a total time of 3 min; S4 - first stage at 70°C for 3 min; S4 - second stage at 95°C for 5 min; S5 - post-curing at 120°C for 0.5 h; and finally, aeration at 60°C for 1 h. This comparative example was used to investigate the synergistic relationship between the pre-dispersion and the distribution of the conductive phase on the pore walls.
[0071] Comparative Example 10: Essentially the same as Example 1, except that deionized water was not added. Other conditions were maintained as follows: 100.00 parts by weight of high-viscosity vinyl-terminated dimethyl polysiloxane, 12.00 parts by weight of conductive carbon black, 3.00 parts by weight of low-viscosity vinyl-terminated dimethyl polysiloxane, 4.00 parts by weight of polymethylhydrosiloxane, 0.20 parts by weight of hydroxyl-terminated polydimethylsiloxane, 0.01 parts by weight of 1-ethynyl-1-cyclohexanol, and a platinum content of 5%. The following steps were performed: ppm, A2 shear wetting at 25°C for 0.5 h, A3 three-roller dispersion twice with an 80 μm roller gap, S2 stirring at 20°C for 10 min, S3 adding polymethylhydrosiloxane and hydroxyl-terminated polydimethylsiloxane in sequence for a total addition time of 2 min, S3 mixing at 20°C for 5 min, S4 first stage at 70°C for 3 min, S4 second stage at 95°C for 5 min, S5 post-curing at 120°C for 0.5 h, and ventilating at 60°C for 1 h. This comparative example was used to investigate the synergistic relationship between deionized water and the curing pore-forming process.
[0072] Comparative Example 11: Basically the same as Example 1, except that before step A2, dried conductive carbon black was pre-contaminated with 0.10 parts by weight of deionized water for 30 minutes before adding low-viscosity vinyl-terminated dimethyl polysiloxane for shear wetting. Other conditions were maintained as follows: 100.00 parts by weight of high-viscosity vinyl-terminated dimethyl polysiloxane, 12.00 parts by weight of conductive carbon black, 3.00 parts by weight of low-viscosity vinyl-terminated dimethyl polysiloxane, 4.00 parts by weight of polymethylhydrosiloxane, 0.20 parts by weight of hydroxyl-terminated polydimethylsiloxane, and 1-ethynyl-1- Cyclohexanol 0.01 parts by weight, platinum content 5 ppm, A2 shear wetting at 25°C for 0.5 h, A3 three-roll dispersion twice with an 80 μm roller gap, S2 stirring at 20°C for 10 min, step S3 adding polymethylhydrosiloxane, hydroxyl-terminated polydimethylsiloxane, and deionized water in the same order, with 0.10 parts by weight of deionized water in step S3, and a total addition time of 3 min, S4 first stage at 70°C for 3 min, S4 second stage at 95°C for 5 min, S5 post-curing at 120°C for 0.5 h, and ventilated treatment at 60°C for 1 h. This comparative example was used to investigate the effect of contacting conductive carbon black with deionized water before pre-dispersion on the wetting and dispersion of conductive carbon black.
[0073] Characterization and performance testing: Using sheet-like or pad-like piezoresistive conductive silicone from Examples 1–4 and all comparative examples as subjects, the primary micropore D50, secondary pore window D50, and porosity were evaluated. The testing principle was statistical microscopy. Samples were cold-cut along their thickness direction, sputter-coated with gold, or observed under low vacuum. Surface and cross-sectional images were acquired. For each sample, at least 300 primary micropores and 300 secondary pore windows were counted. Pore structures with cavity morphology were defined as primary micropores, and the openings or narrow channels connecting adjacent primary micropores were defined as secondary pore windows. These were counted using equivalent circle diameters. D50 and D90 were the pore sizes or agglomerate particle sizes corresponding to 50% and 90% of the total equivalent circle diameter, respectively, after sorting by diameter from smallest to largest. Porosity was calculated using statistical microscopy. Data records include the mean D50 of primary micropores, the standard deviation of D50 of primary micropores, the mean D50 of secondary pore windows, the standard deviation of D50 of secondary pore windows, the mean porosity, and the standard deviation of porosity, in units of μm and vol%, respectively, n≥3.
[0074] Using cut sheets of each sample as the research object, the volume resistivity and coefficient of variation of in-plane resistance were evaluated. The volume resistivity test followed the applicable approach of ASTM D991, "Standard Test Method for Rubber Property—Volume Resistivity of Electrically Conductive and Antistatic Products," using a parallel electrode fixture to measure the resistance in the thickness direction at 25°C and 50% relative humidity. The volume resistivity was calculated using ρ=RA / d, where R is the stable resistance value in the thickness direction, A is the effective electrode contact area, and d is the sample thickness. For the in-plane direction, 10–100 measuring points were arranged, and the in-plane resistance value at each measuring point was measured under the same test conditions. The coefficient of variation of in-plane resistance was calculated by dividing the standard deviation of the in-plane resistance value at each measuring point by the average value of the in-plane resistance value at each measuring point, and then multiplying by 100%. The experiment yielded the mean volume resistivity, the standard deviation of volume resistivity, and the mean and standard deviation of the coefficient of variation of in-plane resistance, in units of Ω·cm and %.
[0075] Using the electrode clamping samples from the examples and comparative cases, the piezoresistive sensitivity within a pressure range of 10–100 kPa was evaluated. The test principle involved measuring the change in the conductive path caused by pore wall deformation under progressively compressive loads, and recording the relationship between pressure and relative resistance changes. The samples were equilibrated at 25°C for 24 h, and held at 10, 20, 40, 60, 80, and 100 kPa for 30 s, with the stable resistance recorded. The rate of change of relative resistance was calculated based on the initial resistance under no-load conditions, and a linear fit was performed between the rate of change of relative resistance and pressure. The mean piezoresistive sensitivity, standard deviation of piezoresistive sensitivity, linear correlation coefficient, and hysteresis rate were obtained experimentally, in kPa. -1 , dimensionless and %, n≥3.
[0076] Using samples cut from the same batch, the compression modulus and compression set were evaluated. The compression modulus was tested according to the applicable approach in ASTM D575 for testing the compression properties of rubber, compressing the sample at a constant loading rate to the target strain at 25°C and recording the stress-strain curve. The compression set was tested according to the applicable approach in ASTM D395 for testing the compression set of rubber, recording the thickness change before and after compression. The mean compression modulus, standard deviation of compression modulus, mean and standard deviation of compression set were obtained, in kPa and %, respectively, with n≥3.
[0077] The initial resistance drift rate after compression cycling was evaluated using electrode sheet samples. The test principle is that the rearrangement of the conductive carbon black network and pore wall structure after repeated compression and recovery alters the initial resistance. The samples were cycled 10,000, 50,000, 80,000, or 100,000 times at a peak pressure of 50 kPa at 25°C and 50% relative humidity, with a frequency of 1 Hz. The samples were allowed to stand under no-load for 10 minutes before and after each cycle before measuring the initial resistance. The initial resistance drift rate was calculated by dividing the change in initial resistance before and after cycling by the initial resistance before cycling and multiplying by 100%. The experimental results included the number of cycles, the mean initial resistance drift rate, the standard deviation of the initial resistance drift rate, and the response retention rate after cycling, expressed in cycles, percentages, and percentages, with n ≥ 3.
[0078] Using the pre-dispersions of Example 1 and Comparative Example 6, and the conductive silicone premix obtained after mixing in step S2 of Comparative Example 9, the agglomerate D90 of conductive carbon black was evaluated. The agglomerate D90 was obtained by image statistical analysis after each test material was pressed into a thin film. The data fields are the mean and standard deviation of the agglomerate D90, in μm, n≥3.
[0079] Unless otherwise stated, the values of each parameter recorded in this article are the arithmetic mean of the results of n≥3 parallel samples, and the values after "±" are the standard deviations.
[0080] Table 1 Performance of Examples and Comparative Examples
[0081]
[0082] To verify the comprehensive effects of the multi-level microporous piezoresistive conductive silicone and its preparation method described in this invention on conductive carbon black dispersion, pore structure maintenance, conductive network stability, and piezoresistive response, comparative tests were conducted on the materials obtained in the examples and comparative examples. The test results show that, through the synergistic cooperation of steps such as conductive carbon black pre-dispersion, pore formation induced by hydroxyl components and deionized water, and staged foaming and curing of the silicone matrix, this invention can maintain the integrity of the sheet structure while enabling the conductive phase to form a relatively continuous and non-excessively agglomerated distribution in the pore wall region. This alleviates the problem in existing porous conductive silicone where structural integrity, piezoresistive sensitivity, conductive carbon black dispersion stability, and effective conductive contact are difficult to simultaneously achieve.
[0083] First, from the perspective of the dispersion state of the conductive phase, Figure 1 The equivalent particle size distribution of conductive carbon black agglomerates in the predispersants of Comparative Example 1 and Comparative Example 6, and in the conductive silicone premix obtained after mixing in step S2 of Comparative Example 9, was used for comparison. Figure 1It can be seen that the conductive carbon black agglomerates in Example 1 have a more concentrated particle size distribution and a lower D90, indicating that the pre-dispersion of conductive carbon black by low-viscosity vinyl-terminated dimethyl polysiloxane can effectively weaken the secondary agglomeration tendency between carbon black particles. In contrast, the agglomerate particle size distribution in Comparative Examples 6 and 9 shows a shift towards larger particle sizes, indicating that conductive carbon black is more prone to local agglomeration when dispersion conditions are insufficient or the pre-dispersion preparation process is omitted. This result shows that the pre-dispersion step is not simply a mixing step, but a prerequisite for the subsequent formation of a uniform pore-walled conductive network, which is beneficial to improving the spatial distribution stability of the conductive phase in the silica matrix and providing conditions for the repeatability of the piezoresistive response and the consistency of resistance.
[0084] Furthermore, considering the conductivity network retention capability and pore structure stability after cyclic compression, Figures 2 to 4 The data reflect the initial resistance drift, primary micropore D50 variation, and secondary pore window D50 variation of Examples 1, 8, and 10 during 0–10000 compression cycles, respectively. Figure 2 It can be seen that after 10,000 compression cycles, the initial resistance drift rate of Example 1 is approximately 30%, indicating that the conductive pathway can remain relatively stable during repeated compression and release. This result shows that the conductive phase in this invention does not rely solely on random stacking to form conductive pathways, but rather forms a relatively stable contact network under the constraint and bearing effect of the multi-level microporous pore wall skeleton. Therefore, it is not prone to irreversible migration or large-scale fracture after cyclic compression.
[0085] Corresponding to the resistance drift results, Figure 3 The D50 of the primary micropores in Example 1 showed that after 0–10,000 compression cycles, it slowly changed from about 80 μm to about 74 μm. The change was small, indicating that the primary micropore framework can still maintain good dimensional stability and anti-collapse ability after cyclic compression. Figure 4 Further, it is shown that the D50 of the secondary pore windows in Example 1 remains basically within the range of 4.7–5.0 μm, and the pore window size changes gradually, indicating that the secondary interconnected pore structure did not undergo significant closure or irreversible blockage during compression. The primary micropores provide compressible deformation space, while the secondary pore windows provide microscopic connectivity and local contact adjustment channels. Together, they enable the material to undergo effective deformation during compression without causing instability of the conductive network due to pore structure collapse. Therefore, Figures 2 to 4 Both electrical drift and pore structure evolution demonstrate that the multi-level micropore design of this invention can balance compressive deformation capacity and structural integrity.
[0086] Regarding conductivity uniformity, Figure 5The graph shows the coefficient of variation of in-plane resistance, used to compare the dispersion of in-plane resistance of the sheets in Example 1, Comparative Example 8, and Comparative Example 9. The results show that the coefficient of variation of in-plane resistance for Example 1 is approximately 25%, lower than that for Comparative Examples 8 and 9, indicating that Example 1 has a smaller resistance difference between different locations on the sheet. This result is consistent with... Figure 1 The results of the particle size distribution of conductive carbon black agglomerates corroborate each other, indicating that the degree of agglomeration of conductive carbon black is reduced after pre-dispersion treatment, and the dispersion of conductive pathways at different locations on the sheet is reduced accordingly, thereby reducing the non-uniformity of the conductive pathways within the sheet surface. For piezoresistive conductive silicone, a reduced coefficient of variation in in-plane resistance not only means improved consistency in material preparation but also that different pressure-bearing areas have more similar initial conductive states, which is beneficial to improving the reliability of pressure detection results.
[0087] In terms of piezoresistive response performance, Figure 6 This is a pressure-relative resistance change response curve used to compare the rate of change of relative resistance in Examples 1–4 over a pressure range of 10–100 kPa. Figure 6 It can be seen that Examples 1–4 all exhibit continuous and identifiable changes in relative resistance with increasing external pressure, indicating that the conductive network inside the material can be repeatedly modulated according to changes in the contact state of the pore walls, the spacing between conductive phases, and the number of local contact points. Different examples show different response slopes due to differences in formulation ratios and pore structure parameters, indicating that the present invention can not only obtain a single conductive state, but can adjust the piezoresistive response range and response intensity through formulation and process parameters. This result proves that the multi-level microporous conductive silicone formed by the present invention possesses the continuous electrical output capability required for pressure response detection.
[0088] To further clarify the effect of conductive carbon black dosage on piezoresistive sensitivity and resistance stability. Figure 7 Based on the basic formulation and process of Example 1, only the equivalent amount of conductive carbon black was changed, and the changes in material properties were investigated under conditions of 8, 12, 16, 20, 24, 28, and 34 parts by mass. Figure 7It is evident that when the equivalent amount of conductive carbon black is low, the number of conductive contact points is insufficient, the conductive network is inadequate, and the piezoresistive sensitivity of the material is low. When the equivalent amount of conductive carbon black is too high, although the number of conductive fillers increases, it easily leads to excessive contact or local agglomeration between fillers, resulting in excessively low initial resistance, reduced modulation space of the conductive network, and potentially increased resistance drift. In contrast, when the equivalent amount of conductive carbon black is in the range of 16–28 parts by mass, the piezoresistive sensitivity of the material is significantly improved, and the initial resistance drift rate remains at a low level, with the 20–24 parts by mass range showing the best overall performance. This result demonstrates that the present invention, by rationally controlling the amount of conductive carbon black, enables the conductive phase to form an effective contact network while retaining the modulation space required for changes in contact state during compression, thereby avoiding two types of problems: weak response due to insufficient conductive filler and decreased stability due to excessive conductive filler.
[0089] In addition to the quantitative tests mentioned above, Figure 8 Macroscopic optical photographs were taken of the final product of Example 1 and the final product of Comparative Example 9 to evaluate the overall appearance, sheet integrity and macroscopic uniformity of the sheet-like piezoresistive conductive silicone. Figure 8 Image a is a macroscopic optical photograph of the final product of Example 1. The obtained sample is a black sheet-like piezoresistive conductive silicone with a nominal thickness of 0.50 mm. Its primary micropore D50 is 80 ± 6 μm, its secondary pore window D50 is 5.0 ± 0.6 μm, and its porosity is 35.0 ± 1.2 vol%. The above parameters indicate that Example 1 can form a stable multi-level microporous structure in a relatively thin sheet while maintaining the continuity of the sheet and the integrity of the overall molding. Figure 8 b is a macroscopic optical photograph of the final product of Comparative Example 9. Comparative Example 9 did not undergo the preparation process of conductive carbon black-low viscosity vinyl-terminated dimethyl polysiloxane predispersant. Its sheet macroscopic uniformity is weaker than that of Example 1, indicating that the direct addition of conductive carbon black is more likely to cause local color difference, filler enrichment or structural inhomogeneity. Figure 8 The results demonstrate from a macroscopic morphology perspective that the preparation of pre-dispersions helps improve the overall distribution of conductive carbon black in the sheets and is beneficial for obtaining conductive silicone sheets with uniform appearance and complete structure.
[0090] Further observation of the microstructure, Figure 9 Scanning electron microscope morphology of the final product of Comparative Example 1 and the final product of Comparative Example 9. Figure 9 a is a low-magnification scanning electron microscope image of the final product of Example 1. It can be observed that a relatively uniform micropore distribution is formed in the cross-section of the sheet with a nominal thickness of 0.50 mm, indicating that the staged foaming curing and the matching ratio of pore-forming components can enable the formation of a stable multi-level pore structure inside the sheet. Figure 9 b is a low-magnification scanning electron microscope image of the final product of Comparative Example 9, whose pore structure uniformity is weaker than that of Example 1. Figure 9c is a high-resolution scanning electron microscope image of the final product of Example 1, showing that the primary micropores and continuous pore wall structure are relatively clear, and the pore walls can serve as a supporting framework for the attachment and continuous transfer of conductive phase. Figure 9 Image d is a scanning electron microscope image of the final product of Comparative Example 9, which shows relatively insufficient continuity of the pore walls and uniformity of local morphology. Figure 9 The results, from a microscopic morphology perspective, indicate that pre-dispersion preparation helps improve the uniformity of the pore structure and the continuity of the pore walls in the sheet.
[0091] The performance data of the examples and comparative examples in Table 1 show that Examples 1–4 exhibit a good coordination relationship among pore structure parameters, volume resistivity, coefficient of variation of in-plane resistance, piezoresistive sensitivity, compressive modulus, and initial resistance drift rate after cycling. Specifically, the examples, through pre-dispersing conductive carbon black, adjusting the ratio of polymethylhydrosiloxane to hydroxyl components and deionized water, and using staged foaming and curing, enable the material to simultaneously possess a compressible multi-level microporous structure, a relatively stable pore wall skeleton, and a relatively uniform conductive network. In contrast, the conventional comparative examples, after individually changing the conductive carbon black, polymethylhydrosiloxane, deionized water, number of dispersion passes, curing temperature, or ventilation conditions, are prone to problems such as abnormal volume resistivity, increased in-plane resistance dispersion, increased resistance drift after cycling, or insufficient compressive deformation response. The synergistic effect of Comparative Examples 9–11, after disrupting the conductive carbon black pre-dispersion, pore-forming component matching, or non-aqueous phase pretreatment process, shows a more significant decrease in conductive uniformity and cycling stability.
[0092] Therefore, this invention does not achieve piezoresistive response by simply increasing the content of conductive filler or merely increasing porosity. Instead, it achieves this through the synergistic design of the conductive carbon black dispersion state, pore wall skeleton strength, primary micropore deformation space, secondary pore window connectivity structure, and staged curing process. This allows the conductive phase to form a stable, continuous, and modulated conductive network in the multi-level micropore wall regions. The above-mentioned results demonstrate that this invention can simultaneously improve structural integrity, piezoresistive sensitivity, conductive carbon black dispersion stability, and effective conductive contact stability in sheet-like porous conductive silicone, thus providing an effective solution to the technical contradiction of existing porous conductive silicone products that struggle to achieve these performance characteristics simultaneously.
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A piezoresistive conductive silicone with a multi-level microporous structure, characterized in that, Using 100 parts by weight of high-viscosity vinyl-terminated dimethyl polysiloxane as the silicone matrix, the piezoresistive conductive silicone is formed by curing and pore formation of a curable mixture comprising the high-viscosity vinyl-terminated dimethyl polysiloxane and the following components: Conductive carbon black-low viscosity vinyl-terminated dimethyl polysiloxane predispersant, wherein the predispersant contains, on average, 12–28 parts by weight of conductive carbon black and 3–10 parts by weight of low viscosity vinyl-terminated dimethyl polysiloxane. 1.0–5.0 parts by weight of polymethylhydrosiloxane; Hydroxyl-terminated polydimethylsiloxane 0.20–3.00 parts by weight; 1,3-Divinyl-1,1,3,3-Tetramethyldisiloxane platinum (0), in platinum amounts to 5–50 ppm of the total mass of the curable mixture; 0.01–0.20 parts by weight of 1-ethynyl-1-cyclohexanol; 0.10–1.20 parts by weight of deionized water; In the pre-dispersion, the mass ratio of low-viscosity vinyl-terminated dimethyl polysiloxane to conductive carbon black is 15:100 to 60:100; The piezoresistive conductive silicone has a multi-level microporous structure consisting of primary micropores and secondary pore windows.
2. The piezoresistive conductive silicone according to claim 1, characterized in that, The primary micropores have a D50 of 80–350 μm, the secondary pore windows have a D50 of 5–40 μm, a porosity of 35–65 vol%, and a volume resistivity of 10 Ω·cm. 2 -10 5 Ω·cm.
3. The piezoresistive conductive silicone according to claim 1, characterized in that, The pre-dispersion is prepared by the following steps: A1. Dry 100 parts by weight of conductive carbon black at 100–120℃ for 1–3 hours; A2. The conductive carbon black obtained in step A1 is mixed with 15–60 parts by weight of low viscosity vinyl-terminated dimethyl polysiloxane and sheared and wetted at 25–60°C for 0.5–3.0 h to form a carbon black wetted product. A3. The carbon black wetted material is dispersed through a three-roller system 2–5 times, with a roller gap of 20–80 μm; A4. Vacuum degassing for 10–30 min under conditions of -0.09 to -0.06 MPa; A5. Vacuum dry at 40–80℃ for 2–8 h to obtain the pre-dispersion.
4. The piezoresistive conductive silicone according to claim 3, characterized in that, Steps A2 to A5 are non-aqueous phase treatment steps; the D90 of the carbon black agglomerates in the pre-dispersion is 2–25 μm.
5. The piezoresistive conductive silicone according to claim 1, characterized in that, The piezoresistive conductive silicone has a pore structure in which adjacent primary micropores are connected by the secondary pore windows.
6. The piezoresistive conductive silicone according to claim 1, characterized in that, The piezoresistive conductive silicone has at least one of the following product forms or performance characteristics: a. The piezoresistive conductive silicone is a sheet or pad material with a thickness of 0.50–6.00 mm; b. The piezoresistive conductive silicone rubber exhibits a piezoresistive sensitivity of 0.005–0.080 kPa within a pressure range of 10–100 kPa. -1 The coefficient of variation of in-plane resistivity is 5–25%, and the initial resistivity drift rate after 10,000–100,000 compression cycles is 5–30%. c. The piezoresistive conductive silicone has a compression modulus of 20–300 kPa and a compression set of 5–30% in the pressure range of 10–100 kPa.
7. A method for preparing a piezoresistive conductive silicone with a multi-level microporous structure as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Provides a conductive carbon black-low viscosity vinyl-terminated dimethyl polysiloxane predispersant obtained through non-aqueous phase treatment; S2. Mix 100 parts by weight of high viscosity vinyl-terminated dimethyl polysiloxane with the pre-dispersion and stir at 20–50°C for 10–60 min to obtain a conductive silicone premix. S3. Polymethylhydrosiloxane, hydroxyl-terminated polydimethylsiloxane and deionized water are added sequentially to the conductive silicone premix, followed by the addition of 1-ethynyl-1-cyclohexanol and 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum (0), and the mixture is mixed at 20–40°C for 5–30 min to obtain a curable mixture; S4. The curable mixture is introduced into a molding device, and foamed and cured in stages at 70–130°C for 8–40 min to obtain pre-cured multi-level microporous conductive silicone. S5. The pre-cured multi-level microporous conductive silicone is post-cured at 120–170℃ for 0.5–4.0h, and then placed at 60–100℃ for ventilation treatment for 1–8h to obtain a piezoresistive conductive silicone with a multi-level microporous structure.
8. The preparation method according to claim 7, characterized in that, It has at least one of the following process characteristics: a. The stirring in step S2 is planetary stirring, kneading stirring or double planetary vacuum stirring. After stirring, degassing is carried out under conditions of -0.09 to -0.06 MPa for 5–30 min. b. In step S3, the order of adding the polymethylhydrosiloxane, the hydroxyl-terminated polydimethylsiloxane, and the deionized water is as follows: first add the polymethylhydrosiloxane, then add the hydroxyl-terminated polydimethylsiloxane, and finally add the deionized water. The total addition time for the three is 3–20 min.
9. The preparation method according to claim 7, characterized in that, Step S4 includes a first stage and a second stage, wherein the first stage is maintained at 70–95°C for 3–15 min and the second stage is maintained at 95–130°C for 5–25 min.
10. The preparation method according to claim 7, characterized in that, When the forming device used in step S4 is a mold, the closing pressure of the mold is 0.05–1.00 MPa, and the thickness of the mold cavity is 0.50–6.00 mm.
Citation Information
Patent Citations
Carbon black filled pressure-sensitive conductive silicone rubber composite material and preparation method thereof
CN105001641A
